2022
DOI: 10.18240/ijo.2022.08.09
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and predictors of vitrectomy and silicone oil tamponade in retinal detachments complicated by proliferative vitreoretinopathy

Abstract: AIM: To evaluate outcomes and determine factors influencing the outcomes of vitrectomy with silicone oil (SO) endotamponade for the management of rhegmatogenous retinal detachment (RRD) complicated by advanced proliferative vitreoretinopathy (PVR). METHODS: This is a retrospective, interventional case series of eyes with PVR grade C associated RRD with or without prior surgery that underwent vitreoretinal surgery and SO tamponade. Eyes with a minimum follow-up of 6mo after SO extraction were included. Eyes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
5
1
Order By: Relevance
“…In 2005, Pastor et al [10] devised a statistical model specifically for patients with RD repair surgery to assess the probability of PVR. Although the sensitivity and specificity of this model were higher than those of previous studies [9,11] , the optimal values were still only 78.0% and 75.6%, respectively. Later, Wickham et al [12] developed a simplified formula to predict the risk for PVR in patients with primary RD after vitrectomy using preoperative clinical data.…”
Section: Internal and External Validation Of The Nomogramcontrasting
confidence: 72%
See 2 more Smart Citations
“…In 2005, Pastor et al [10] devised a statistical model specifically for patients with RD repair surgery to assess the probability of PVR. Although the sensitivity and specificity of this model were higher than those of previous studies [9,11] , the optimal values were still only 78.0% and 75.6%, respectively. Later, Wickham et al [12] developed a simplified formula to predict the risk for PVR in patients with primary RD after vitrectomy using preoperative clinical data.…”
Section: Internal and External Validation Of The Nomogramcontrasting
confidence: 72%
“…In addition, the majority of postoperative PVR were grade B (94.0%), which was less serious and did not affect the final surgical success rate. Previous studies reported different results on whether tamponade (SO or gas) was a risk factor for PVR [11,19,[23][24] . In the present study, the type of tamponade (SO or C 3 F 8 ) was not associated with postoperative PVR.…”
Section: Internal and External Validation Of The Nomogrammentioning
confidence: 99%
See 1 more Smart Citation
“…I n addition to retinal-related complications [1][2][3][4][5] vitreoretinal surgery can also cause corneal complications [6] , including persistent corneal epithelial defects [7][8][9] , diabetic keratopathy [10][11][12][13] , etc., which are caused by prolonged duration of surgery and intraoperative epithelial debridement. It is well known that corneal edema often occurs during vitreoretinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure may result in postoperatively ocular discomfort, increased incidence of persistent corneal defect or haze formation, particularly in diabetic patients [11,13] . Recently, with the popular use of a noncontact wide-angle viewing system, various viscoelastic corneal lubricants or antidrying contact lenses were developed to avoid drying [4,[15][16][17][18][19][20][21][22][23] . However, they seem powerless to prevent occurrence of corneal edema.…”
Section: Introductionmentioning
confidence: 99%